ANTERIOR CERVICAL RECONSTRUCTION USING TITANIUM MESH CAGES - Shams, Shahzad; Rashid, Muhammad Javaid (Journal of Ayub Medical College Abbottabad, 2007)
Background: Surgical management of cervical lesions with reconstruction procedures has remarkably expanded the options available in the last decade. Anterior cervical corpectomy with titanium mesh reconstruction is one of the effective method of cervical spine reconstruction. Methods: We studied 17 consecutive cases in whom corpectomy and decompression was performed. Fusion with titanium mesh cages filled with local bone pieces were placed inside the cage. Results: Clinical status improved in 13 patients whereas in 3 it remained unchanged, based on Nurick's classification. At 3 months follow up, 13 (76.4%) patients reported successful arm pain relief and 12 (70.5% ) with neck pain relief with visual analog score below five. Complications included cage in kyphosis, radiculopathy, cage subsidence and wound infection. Conclusion: Outcome after cervical fusion procedures with a titanium mesh cage lead to early and good stability of the cervical spine, excellent neurological improvement, low risk of complication and rare need for endogenous bone graft harvest avoiding donor site morbidity, less postoperative pain and decreased hospital stay and cost. Keywords: Cervical Spine, Reconstruction, Titanium Mesh Cage